Applications of compressed air energy storage in cogeneration systems - Vieira, Felipe Seabra [UNESP] (2021)
Cogeneration is a technology related to energy efficiency, but it is not enough to deal with the integration of renewable sources to the grid and meeting fluctuating demands. Compressed air energy storage is a promising technology that can be aggregated within cogeneration systems in order to keep up with those challenges. Here, we present different systems found in the literature that integrate compressed air energy storage and cogeneration. The main parameters of performance are reviewed and analyzed. Among the systems found, GT-S-CAES-ORC presented the best exergy efficiency, suggesting a trend towards systems integrating gas turbines and organic Rankine cycles. SC-CAES seems to be the most efficient in terms of the first law, with reasonable values of exergy efficiency. Regarding some parameters of performance, data and information required to calculate them is not widely available yet, so that new studies should consider these parameters. Besides, none of the parameters found is universally adopted, so that future studies should be focused on the creation of a new parameter of performance for cogeneration systems with CAES. Most of the reviewed works are theoretical, so in the medium term future, it should be expected more laboratory prototypes and pilot plants.